2006
DOI: 10.1074/jbc.m512307200
|View full text |Cite
|
Sign up to set email alerts
|

Endosome Sorting and Autophagy Are Essential for Differentiation and Virulence of Leishmania major

Abstract: Cellular remodeling during differentiation is essential for lifecycle progression of many unicellular eukaryotic pathogens such as Leishmania, but the mechanisms involved are largely uncharacterized. The role of endosomal sorting in differentiation was analyzed in Leishmania major by overexpression of a dominant-negative ATPase, VPS4. VPS4 E235Q accumulated in vesicles from the endocytic pathway, and the mutant L. major was deficient in endosome sorting. Mutant parasites failed to differentiate to the obligate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
273
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(288 citation statements)
references
References 53 publications
14
273
1
Order By: Relevance
“…TcAtg4.2 may, thus, be an orphan protease remaining in the genome and eventually serving as a backup system, although the possibility that TcAtg4.2 might be involved in the processing and/or deconjugation of other ubiquitin-like proteins remains open. A recent study performed in L. major suggested the LmATG4.2 gene to be important for autophagy and differentiation (46). The L. major atg4.2⌬ mutants had an increased proportion of the lipidated form of Atg8 relative to the unlipidated one, which led to speculation for a role of Atg4.2 in Atg8 deconjugation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TcAtg4.2 may, thus, be an orphan protease remaining in the genome and eventually serving as a backup system, although the possibility that TcAtg4.2 might be involved in the processing and/or deconjugation of other ubiquitin-like proteins remains open. A recent study performed in L. major suggested the LmATG4.2 gene to be important for autophagy and differentiation (46). The L. major atg4.2⌬ mutants had an increased proportion of the lipidated form of Atg8 relative to the unlipidated one, which led to speculation for a role of Atg4.2 in Atg8 deconjugation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CPA and CPB from Leishmania mexicana were recently found to be essential for both autophagosome degradation and differentiation of that parasite. In addition, LmAtg4.2 was suggested to be involved in autophagosome formation, thus being upstream of CPA and CPB (39,46).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 GFP-labeled autophagosomes were observed colocalizing with RFP-SQL-labeled glycosomes during promastigote log phase, stationary phase, and starvation ( Fig. 2A; Table S1), suggesting that glycosomes constitute autophagosome cargo in Leishmania.…”
Section: Analysis Of Glycosome Turnover By Autophagymentioning
confidence: 99%
“…Further characterization showed that Leishmania expressing GFP-ATG8 form GFP-labeled puncta corresponding to autophagosomes and that autophagy is induced by starvation, as in yeast and mammals, as well as increasing during differentiation. 20,21 During procyclic to metacyclic promastigote differentiation, GFP-ATG8 appears in tubular structures resembling the MVT-lysosome and the PEconjugated form of ATG8 is more abundant as shown by western blotting. Leishmania with defects in the autophagy pathway, either overexpressing a dominant-negative VPS4, important in endosomal sorting pathways, 21 or lacking the major lysosomal peptidases CPA and CPB, 20 are unable to fully differentiate, in addition to being unable to survive prolonged starvation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation